Treatment of skeletal class II division 1 malocclusion with mandibular deficiency using myofunctional appliances in growing individuals - Y Pachori; M Navlani; T Gaur; S Bhatnagar (Wolters Kluwer Medknow Publications, 2012)
Class II division 1 malocclusion is the most common malocclusion seen in day-to-day practice. The majority of the patients with class II division 1 malocclusions have the presence of underlying skeletal discrepancy between maxilla and mandible. The treatment of skeletal class II division 1 depends upon the age of the patient, growth potential, severity of malocclusion, and compliance of patient with treatment. Myofunctional appliance can be successfully used to treat growing patients with class II division 1 malocclusion having retrusive mandible. This article presents a discussion on treatment of class II division 1 due to mandibular deficiency with growth modification approach using myofunctional appliances and a series of three case reports of treatment of skeletal class II division 1 malocclusion using myofunctional appliance followed by fixed mechanotherapy.